Phytochemical study of Helichrysum italicum (Roth) G. Don: Spectroscopic elucidation of unusual amino-phlorogucinols and antimicrobial assessment of secondary metabolites from medium-polar extract. (December 2016) - D'Abrosca, Brigida; Buommino, Elisabetta; Caputo, Pina; Scognamiglio, Monica; Chambery, Angela; Donnarumma, Giovanna; Fiorentino, Antonio
Abstract: Three unusual amino-phloroglucinols, named helichrytalicines A-C, along with seventeen known compounds including acetophenones, tremetrone derivatives, low-molecular weight phenols, flavonol glucosides, have been isolated from the medium-polar extract of Helichrysum italicum (Roth) G. Don, a medicinal plant typical of the Mediterranean vegetation. The structures of the compounds have been elucidated based on extensive 2D-NMR spectroscopic analyses, including COSY, TOCSY, HSQC, CIGAR-HMBC, H2BC and HSQC-TOCSY, along with Q-TOF HRMS 2 analysis. Stereostructure of the new compounds has been elucidated by Mosher's method and NOESY experiment. Antimicrobial properties against Staphylococcus epidermidis of selected compounds have been evaluated. Graphical abstract: Highlights: Three unusual amino-phlorogucinols have been isolated from medicinal plant Helicrysum italicum . Structures were elucidated by 2D-NMR and Q-TOF HRMS 2 analyses. Selected compounds were evaluated for their anti-biofilm properties against Staphylococcus epidermidis.